Evaluation of Foundations of Language and Linguistics Using the CIPP Model - Paudel, Kamal (Journal of Advanced Research in English & Education, 2025)
Purpose: This study evaluates the Foundations of Language and Linguistics course (English Education 416) from the B.Ed. First Year program at Tribhuvan University using Stufflebeam’s (1983) CIPP model. The research aims to assess the course structure, content delivery, and its alignment with the intended learning outcomes. Methodology: A qualitative research design was employed, with purposive sampling to select two B.Ed. graduates and two course instructors as participants. Data were collected through semi-structured interviews, curriculum and syllabus analysis, and document reviews. Findings: The findings indicated significant deficiencies in both the course structure and the delivery of its contents. Key issues identified included the lack of coordination between theory and practice in classroom teaching, which hindered the fulfillment of the course’s general and specific objectives. The study also highlighted the need for earlier introduction of linguistic concepts, a more logical and chronological sequence of content, and updated materials with practical examples and interactive activities. Additionally, the current assessment strategies and teaching methods, which heavily rely on traditional lectures, were found ineffective in achieving meaningful student learning outcomes. Conclusions: The course requires a comprehensive update, including a better alignment between theory and practice, integration of real-life learning content, and improved teaching methodologies. It is recommended to incorporate practical activities, enhance resource availability, and adopt more creative and interactive teaching approaches to improve both student engagement and academic outcomes.